The relationship between attitudes to homelessness and perceptions of caring behaviours: a cross-sectional study among women experiencing homelessness, nurses and nursing students - Sophie Nadia Gaber; Andreas Karlsson Rosenblad; Elisabet Mattsson; Anna Klarare (BMC, 2022)
Abstract Background Women experiencing homelessness have complex and multifaceted healthcare needs and yet they are an underserved population across healthcare services. Nurses are trained to perform an integral role in the provision of equitable healthcare and their attitudes towards homelessness may therefore influence the care that women experiencing homelessness receive. This study aimed to examine correlations between attitudes towards homelessness and caring behaviours, and to test if these correlations differed between the groups of women experiencing homelessness, registered nurses, and nursing students. Methods A cross-sectional design using convenience sampling was used to recruit women experiencing homelessness (n = 37), registered nurses (n = 90), and nursing students (n = 138) in Stockholm, Sweden between August 2019 and December 2020. The participants answered two questionnaires: the Attitudes Toward Homelessness Inventory and the Caring Behaviours Inventory-24. Correlations between ordinal variables were calculated using Spearman's rank correlation ρ. Tests of equality between two independent correlations were performed using a Z-test applied to Fisher's z-transformed correlations. An advisory board of women with lived experience of homelessness supported the interpretation of the results. Results Weak, negative correlations were identified between the Attitudes Toward Homelessness Inventory and Caring Behaviours Inventory-24. The Attitudes Toward Homelessness Inventory mean total scores (SD) were 4.1 (0.6), 4.2 (0.6), 4.1 (0.5) points for the women experiencing homelessness, registered nurse, and nursing student groups, respectively, with the corresponding scores for the Caring Behaviours Inventory-24 being 4.1 (1.1), 5.2 (0.5), 4.8 (0.7) points, respectively. Conclusions To promote equitable health for women experiencing homelessness, healthcare providers and nurse educators should consider the role of stigmatising attitudes in relation to caring behaviours.